2021
DOI: 10.1002/mcf2.10134
|View full text |Cite
|
Sign up to set email alerts
|

Hatchery‐Origin Stray Rates and Total Run Characteristics for Pink Salmon and Chum Salmon Returning to Prince William Sound, Alaska, in 2013–2015

Abstract: Pacific salmon hatcheries support important commercial fisheries for Pink Salmon Oncorhynchus gorbuscha and Chum Salmon O. keta in Prince William Sound (PWS), Alaska. State policy mandates that hatchery-produced fish must not negatively impact natural populations, which can occur during mixed fisheries and via ecological and genetic interactions. Therefore, we quantified the spatial and temporal overlap of natural-and hatcheryorigin salmon (1) as they migrated into PWS and (2) in PWS spawning streams. Intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 48 publications
(80 reference statements)
6
55
0
Order By: Relevance
“…Piston and Heinl (2012a, 2012b) did not generate estimates for all of SEAK. Knudsen et al (2021) found comparable regionwide pHOS for PWS Chum Salmon: 0.03 in 2013 and 2014 and 0.09 in 2015. This study provides the most appropriate context for understanding the results of our study of SEAK Chum Salmon straying.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Piston and Heinl (2012a, 2012b) did not generate estimates for all of SEAK. Knudsen et al (2021) found comparable regionwide pHOS for PWS Chum Salmon: 0.03 in 2013 and 2014 and 0.09 in 2015. This study provides the most appropriate context for understanding the results of our study of SEAK Chum Salmon straying.…”
Section: Discussionmentioning
confidence: 73%
“…We saw no consistent pattern in the interannual variation in pHOS by stream. Studies in PWS have shown similar results, with some streams exhibiting occasional high stray fractions of hatchery Chum Salmon in some years and then low fractions in other years (Brenner et al 2012; Knudsen et al 2021).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations